Observation of a narrow pentaquark state, Pc(4312)+, and of the two-peak structure of the Pc(4450)+ - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2019)
A narrow pentaquark state, Pc(4312)+, decaying to J/ψp, is discovered with a statistical significance of 7.3σ in a data sample of Λ0b→J/ψpK− decays, which is an order of magnitude larger than that previously analyzed by the LHCb Collaboration. The Pc(4450)+ pentaquark structure formerly reported by LHCb is confirmed and observed to consist of two narrow overlapping peaks, Pc(4440)+ and Pc(4457)+, where the statistical significance of this two-peak interpretation is 5.4σ. The proximity of the Σ+c¯D0 and Σ+c¯D*0 thresholds to the observed narrow peaks suggests that they play an important role in the dynamics of these states.
LHCb Collaboration: R. Aaij, C. Abellán Beteta, B. Adeva, M. Adinolfi, C. A. Aidala, Z. Ajaltouni, S. Akar, P. Albicocco, J. Albrecht, F. Alessio, M. Alexander, A. Alfonso Albero, G. Alkhazov, P. Alvarez Cartelle, A.A. Alves, S. Amato, Y. Amhis, L. An, L. Anderlini
Im Titel ist das kleine c beide Male tiefgestellt, das Pluszeichen jeweils hochgestellt
Gesehen am 17.01.2020